Pengaruh Globalisasi Ekonomi, Industrialisasi, Inovasi Teknologi, dan Kebijakan Energi terhadap Produktivitas Degradasi Lingkungan di Negara-Negara G7 (2014–2023 - Muhammad Nurrosid; Riskiana Elina; Avien Zakaria (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
Introduction: Environmental degradation remains a critical challenge for G7 countries, despite their strong economic capacity, technological advancement, and climate commitments. This study examines environmental degradation productivity, measured by CO₂ emissions per unit of GDP, to capture the carbon intensity of economic output. Methods: This study uses panel data from seven G7 countries during 2014–2023, with 70 country-year observations. The independent variables include Information and Communication Technology (ICT), industrialization, technological innovation, and renewable energy consumption. Panel data regression is applied, and the Random Effect Model is selected based on model specification tests. Results: The findings show that ICT has a negative and significant effect on environmental degradation productivity, indicating that digital transformation supports environmental efficiency. Technological innovation has a positive and significant effect, suggesting a possible rebound effect. Industrialization has a positive but insignificant effect, while renewable energy consumption shows a positive and weakly significant effect. Discussion: These results imply that reducing carbon intensity in G7 countries requires stronger digital integration, green-oriented innovation, industrial decarbonization, and deeper renewable energy substitution. General innovation and renewable energy expansion alone may not reduce environmental degradation unless they effectively replace carbon-intensive systems.